Tren Pendidikan Lingkungan pada Anak Usia Dini: Analisis Bibliometrik Tahun 2000–2025 - Ahmad Fanbudy; Husnul Khotimah; Rafeah Husni; Yuni Sarah (Prodi Pendidikan Islam Anak Usia Dini Sekolah Tinggi Agama Islam Negeri Mandailing Natal- Sumatera Utara, 2025)
This study aims to analyze the trends and development of research on environmental education in early childhood from 2000 to 2025 using a bibliometric approach. Data were obtained from the Scopus database, with approximately 293 documents that met the inclusion criteria. The analysis was conducted using VOSviewer and Biblioshiny to identify publication trends, journal distribution, authors, affiliations, countries, and keyword networks. The results indicate a significant increase in publications, particularly after 2020. Sustainability (Switzerland) emerged as the leading publication source, while authors and institutions were distributed globally, with a dominance of United States and Australia. Subject area analysis revealed that Social Sciences and Psychology were the most dominant fields, whereas the contribution of Environmental Science remained relatively limited. Keyword visualization showed that environmental education is the central theme, evolving toward environmental literacy and sustainable development. These findings suggest that research on environmental education in early childhood is increasingly oriented toward sustainability and environmental literacy, although deeper integration of ecological approaches is still needed. This study provides a comprehensive overview of the research landscape and serves as a reference for future studies. Abstrak Penelitian ini bertujuan untuk menganalisis tren dan perkembangan penelitian pendidikan lingkungan pada anak usia dini dalam rentang waktu 2000–2025 menggunakan pendekatan bibliometrik. Data diperoleh dari basis data Scopus dengan total 126 dokumen yang memenuhi kriteria inklusi. Analisis dilakukan menggunakan perangkat VOSviewer dan Biblioshiny untuk mengidentifikasi tren publikasi, distribusi jurnal, penulis, afiliasi, negara, serta jaringan kata kunci. Hasil penelitian menunjukkan bahwa publikasi mengalami peningkatan signifikan terutama setelah tahun 2020. Jurnal Sustainability (Switzerland) menjadi sumber publikasi utama, sementara penulis dan institusi berasal dari berbagai negara dengan dominasi United States dan Australia. Analisis bidang ilmu menunjukkan dominasi Social Sciences dan Psychology, sedangkan kontribusi Environmental Science masih terbatas. Visualisasi kata kunci menunjukkan bahwa environmental education menjadi tema utama yang berkembang menuju konsep environmental literacy dan sustainable development. Temuan ini mengindikasikan bahwa penelitian pendidikan lingkungan pada anak usia dini semakin berkembang ke arah penguatan literasi lingkungan dan keberlanjutan, namun masih memerlukan integrasi pendekatan ekologi yang lebih mendalam. Penelitian ini diharapkan dapat memberikan gambaran komprehensif mengenai perkembangan literatur serta menjadi dasar bagi pengembangan penelitian selanjutnya.